Redox properties of cytochrome p450BM3 measured by direct methods. - Fleming, B; Tian, Y; Bell, S; Wong, L; Urlacher, V; Hill, H (2003)
Cytochrome p450BM3 is a self-sufficient fatty acid monooxygenase consisting of a diflavin (FAD/FMN) reductase domain and a heme domain fused together in a single polypeptide chain. The multidomain structure makes it an ideal model system for studying the mechanism of electron transfer and for understanding p450 systems in general. Here we report the redox properties of the cytochrome p450BM3 wild-type holoenzyme, and its isolated FAD reductase and p450 heme domains, when immobilized in a didodecyldimethylammonium bromide film cast on an edge-plane graphite electrode. The holoenzyme showed cyclic voltammetric peaks originating from both the flavin reductase domain and the FeIII/FeII redox couple contained in the heme domain, with formal potentials of -0.388 and -0.250 V with respect to a saturated calomel electrode, respectively. When measured in buffer solutions containing the holoenzyme or FAD-reductase domain, the reductase response could be maintained for several hours as a result of protein reorganization and refreshing at the didodecyldimethylammonium modified surface. When measured in buffer solution alone, the cyclic voltammetric peaks from the reductase domain rapidly diminished in favour of the heme response. Electron transfer from the electrode to the heme was measured directly and at a similarly fast rate (ks' = 221 s-1) to natural biological rates. The redox potential of the FeIII/FeII couple increased when carbon monoxide was bound to the reduced heme, but when in the presence of substrate(s) no shift in potential was observed. The reduced heme rapidly catalysed the reduction of oxygen to hydrogen peroxide.